Succinyl-CoA:acetate CoA-transferase functioning in the oxidative tricarboxylic acid cycle in Desulfurella acetivorans - Pettinato, Eugenio; Böhnert, Pauline; Berg, Ivan A. (Frontiers in Microbiology, 2022)
Desulfurella acetivorans is a strictly anaerobic sulfur-reducing deltaproteobacterium that possesses a very dynamic metabolism with the ability to revert the citrate synthase version of the tricarboxylic acid (TCA) cycle for autotrophic growth (reversed oxidative TCA cycle) and for acetate oxidation (oxidative TCA cycle). Here we show that for heterotrophic growth on acetate D. acetivorans uses a modified oxidative TCA cycle that was first discovered in acetate-oxidizing sulfate reducers in which a succinyl-CoA:acetate CoA-transferase catalyzes the conversion of succinyl-CoA to succinate, coupled with the activation of acetate to acetyl-CoA. We identified the corresponding enzyme in this bacterium as the AHF96498 gene product and characterized it biochemically. Our phylogenetic analysis of CoA-transferases revealed that the CoA-transferase variant of the oxidative TCA cycle has convergently evolved several times in different bacteria. Its functioning is especially important for anaerobes, as it helps to increase the energetic efficiency of the pathway by using one enzyme for two enzymatic reactions and by allowing to spend just one ATP equivalent for acetate activation.